Resiliensi Istri Tentara (TNI-AD) Yang Tinggal di Asrama Ketika Suami Bertugas di Daerah Konflik - Fransiska Erna Damayanti (PROFESSIONAL HEALTH JOURNAL, 2019)
Separated from husbands because of their assignment is not easy for the wives, many problems that will be faced by the wives related to changes of roles and responsibilities in the family. Resilience is needed by the military wives in facing many problems, so that they can live well. This is a qualitative research with an interpretive phenomenological approach. Data was collected by in-depth interviews with 6 participants, namely the military wives in accordance with the research criteria. The research results were analyzed using IPA (Interpretive Phenomenological Analysis) This study produced 6 themes, namely: understanding the husband's assignment, feeling proud but worried when the husbands were on duty, facing sorrow as military wives, difficulty in replacing the fathers’ roles in caring for children, trying to find support, adapting to difficult conditions. The six themes finally rise to one big theme, namely the resilience of military wives to be able to achieve family stability. Based on this study, it can be concluded that the main requirements for people to survive any problems in their life is the resilience. Resilience is formed by 3 things: I am (individual factor), I have (support) and I can (ability possessed)